Implementasi Corporate Social Responsibility (CSR) PT. Tri Bakti Sarimas dalam Meningkatkan Kesejahteraan Masyarakat - Saputra, Relly Anjar Vinata Wisnu (LITERAKOM: Jurnal Literasi dan Komunikasi, 2023)
The research was conducted to analyze the implementation of Corporate Social Responsibility/CSR of PT. Tri Bakti Sarimas in order to improve the welfare of the people of Kuantan Singingi Regency, Riau Province. This research is qualitative research, with acase study approach. The informant selection technique used is a purposive technique. This technique includes people who are selected based on certain criteria or categories that are made according to the needs of the research objectives. Data collection techniques are carried out by interviews, observations, and literature studies. Data analysis techniques are carried out with Miles and Huberman data analysis techniques. The analysis was carried out in 3 stages, including 1) data reduction; 3) presentation of data and 4) drawing conclusions. The results showed that PT. Tri Bakti Sarimas is still a donation or voluntary from the company. The CSR program implemented is still far from the ideals of CSR that have been echoed by the government and the international community because the CSR program implemented is not a CSR program that supports the implementation of sustainable economic development.